The roles of dispersal and mass extinction in shaping palm diversity across the Caribbean. (18th April 2018) - Cano, Ángela; Bacon, Christine D.; Stauffer, Fred W.; Antonelli, Alexandre; Serrano‐Serrano, Martha L.; Perret, Mathieu
Abstract: Aim: The rich flora of the Caribbean islands and surrounding mainland evolved in a context of isolation alternated with phases of terrestrial connectivity between landmasses, climatic fluctuations and episodes of mass extinctions during the Cenozoic. We explored how these events affected the evolution of the sister palm tribes Cryosophileae and Sabaleae, and how continent‐island exchanges, endemic radiations and mass extinction shaped their extant diversity. Location: The American continent including the Caribbean region. Methods: We reconstructed a time‐calibrated phylogeny of the palm tribes Cryosophileae and Sabaleae using 84% of the known species. We inferred ancestral distribution and tested the effect of island colonization and mass extinction on extant diversity. Results: Our results indicate that Cryosophileae and Sabaleae originated c . 77 Ma most probably in Laurasia, and their extant species started to diversify between 56–35 Ma and 19–10 Ma respectively. Biogeographical state reconstruction estimated that Cryosophileae dispersed to South America between 56–35 Ma, then dispersed to North‐Central America between 39–25 Ma and the Caribbean islands between 34–21 Ma. We detected a possible signature of a mass extinction event at the end of the Eocene, affecting the diversification of Cryosophileae and Sabaleae and we did not detect a diversification rate shift related to the colonization of the Caribbean islands. Main conclusions: Species of Cryosophileae in the Caribbean islands are probably derived from a single Oligocene dispersal event that likely occurred overwater from North‐Central America rather than through the hypothesized GAARlandia land bridge. Contrastingly, three independent Miocene dispersal events from North‐Central America explain the occurrence of Sabaleae in the Caribbean islands. Contrary to our expectations, island colonization did not trigger increased diversification. Instead, we find that diversification patterns in this clade, and its disappearance from northernmost latitudes, could be the signature of a mass extinction triggered by the global temperature decline at the end of the Eocene.